Políticas públicas de renúncias fiscais no estado do Ceará, com foco nos programas de recuperação fiscal-Refis no período de 2013 a 2016: uma análise do comportamento fiscal - Santos, Jorge Carvalho dos (2024)
The state of Ceará, under different governments, through legal means and with the aim of increasing its tax revenue, uses strategies such as launching tax debt regularization programs in which, normally, taxpayers in debt regularize their situation and can be exempted from fines, interest and other charges and, in many cases, can pay overdue taxes in installments of up to 120 months. Within this permission, we seek to analyze the tax waivers, qualified as Public Tax Policies (PPT) that occurred in the state of Ceará in the period from 2013 to 2016, indicating and correlating this fiscal behavior with factors that indicate the need for more effective planning, under penalty of ending in social losses or even causing destabilization of commercial activity. Thus, analyzing the measures of the public policies discussed, goes through several nuances in which the Refis issue is identified, from the qualitative perspective identified from quantitative data released by government agencies, which show the Fiscal Recovery Program in the state, its concepts and objectives, legal mechanisms that achieve the effects of the extinction of the tax obligation and movement of public coffers.